If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -84 = 2(6 + 8a) -84 = (6 * 2 + 8a * 2) -84 = (12 + 16a) Solving -84 = 12 + 16a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16a' to each side of the equation. -84 + -16a = 12 + 16a + -16a Combine like terms: 16a + -16a = 0 -84 + -16a = 12 + 0 -84 + -16a = 12 Add '84' to each side of the equation. -84 + 84 + -16a = 12 + 84 Combine like terms: -84 + 84 = 0 0 + -16a = 12 + 84 -16a = 12 + 84 Combine like terms: 12 + 84 = 96 -16a = 96 Divide each side by '-16'. a = -6 Simplifying a = -6
| x+3=(x-3)(x-3) | | 3a-45b*j=2 | | 5x+30=11x+48 | | w+(3+w)=25 | | z-3z=8z-7-2 | | 150n-50=100+325 | | 7x^2+12=25x | | -67+6x=-6(-x+7)-4 | | 4x^2-6x=4x^2-3x-27 | | 7x+10=6x+3 | | -9y^2-6y^2+y^2= | | 7(4y-6)=14 | | 4x-3(0)=17 | | -120x=-60 | | -6g=-30 | | 9=X*44 | | -5(4t-4)+6t=8t-9 | | c+(5+c)=33 | | 8-4(2+l)= | | q-21=-7 | | 0=4(0)+7 | | -2(1-4x)+2x=-82 | | 6y+6-5=7 | | 2/5=3/4+y | | -7/3*-11/3=9 | | X^2-2y+x=10 | | -2(t-4)+9t=4t-7 | | b+(-26)=-51 | | 6x^2-60m+10=0 | | 6(x-1)=6x+3-2(-9x-3) | | 43x-7=36 | | b+(2+b)=34 |